Effectiveness of Learning With PBL Model Based on E-Modules to Improve Critical Thinking Skills - Aulia Betha Novianti; Budi Jatmiko; Binar Kurnia Prahani; Noer Risky Ramadhani (Journal of Digitalization in Physics Education, 2025)
Objective: This study aims to examine the effectiveness of physics e-modules based on the Problem-Based Learning (PBL) model in improving students’ critical thinking skills on static fluid concepts. The focus is to evaluate the implementation of learning, measure the improvement of students’ critical thinking ability, and analyze student responses after applying the PBL-based e-modules. Method: The research employed a proper experimental design with a pre-test and post-test control group, conducted at MA Ma’arif Bangil, Pasuruan, Indonesia. A total sampling technique was used, with class XA as the experimental group and class XB as the control group. Data were collected using observation sheets, pre-test and post-test instruments, and student response questionnaires. Data analysis included N-Gain scores, normality and homogeneity tests, t-tests, and descriptive analysis for student responses. Results: The findings showed that the implementation of PBL-based e-modules reached an average of 91.8% categorized as very good. Students in the experimental class demonstrated a significant improvement in critical thinking skills, with an average N-Gain of 0.512 (moderate), compared to 0.212 (low) in the control group. Furthermore, student responses were predominantly in the “good” and “very good” categories, indicating positive perceptions of the learning approach. Novelty: This study highlights the integration of PBL with interactive e-modules as an innovative learning strategy that not only enhances students’ critical thinking skills but also addresses the limitations of conventional print modules. It provides empirical evidence that digital-based problem-oriented instruction is highly relevant to fostering 21st-century competencies in science learning.